HISTOPATHOLOGICAL SPECTRUM OF BREAST LESIONS: A RETROSPECTIVE OBSERVATIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Breast lesions encompass a wide spectrum of inflammatory, benign proliferative, fibroepithelial, borderline and malignant lesions and histopathology is still fundamental to definitive diagnosis.Materials and Methods: This is a retrospective observational study of the histopathological spectrum of the breast samples received in a tertiary care path lab of three years. The age, sex, laterality, type of specimen, clinical presentation and final histopathological diagnosis were noted in the records of 286 breast specimens. The lesions were divided into non-neoplastic, benign neoplastic, borderline and malignant and the malignant ones were graded according to the modified Bloom-Richardson system.Results: The mean age was 38.7 +/- 15.6 years, with a female predominance (98.6%). A total of 206 cases (72.0%) were benign lesions, 68 cases (23.8%) malignant lesions, 6 cases (2.1%) were borderline phyllodes tumors and 6 cases (2.1%) were inflammatory/non-neoplastic lesions. The commonest benign lesion was fibroadenoma (104/286, 36.4%) followed by fibrocystic change (42/286, 14.7%). Invasive carcinoma of no special type was the commonest malignancy (52/68, 76.5%). Age older than 40 years, skin/nipple changes and positivity of the axillary nodes were significantly associated with malignancy (p